Crystal structure of the co-crystal 2-[(2-carboxyphenyl)disulfanyl]benzoic acid – 3-chlorobenzoic acid (2/1), C35H25ClO10S4 - Tan, Sang Loon *; Tiekink, Edward R. T. * (de Gruyter, 2019)
The molecular structure is shown in the figure. Tables 1 and 2, respectively, contain details on crystal characteristics and measurement conditions, and a list of the atoms including atomic coordinates and displacement parameters.